2016
DOI: 10.3892/mco.2016.843
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of totally laparoscopic distal gastrectomy for gastric cancer in elderly patients

Abstract: Abstract. Elderly patients are often considered as high-risk for major abdominal surgery due to reduced functional reserve and increased comorbidities. We herein evaluated the efficacy of totally laparoscopic distal gastrectomy (TLDG) in elderly patients with gastric cancer by measuring the postoperative systemic responses and postoperative analgesic consumption. A total of 102 patients with gastric cancer [57 who underwent TLDG and 45 who underwent laparoscopy-assisted distal gastrectomy (LADG)] were enrolled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
(25 reference statements)
1
4
0
Order By: Relevance
“…Consistent with the present study, they found no severe perioperative complications caused by carbon dioxide pneumoperitoneum in elderly patients who had significantly higher ASA scores. Several studies have also reported that laparoscopic gastrectomy is safe for elderly as well as for non-elderly patients in short-term surgical outcome (10,11,(33)(34)(35). In addition, we found no significant differences in intraoperative blood loss, operative time and complications after surgery between the elderly and non-elderly groups.…”
Section: Discussionsupporting
confidence: 65%
“…Consistent with the present study, they found no severe perioperative complications caused by carbon dioxide pneumoperitoneum in elderly patients who had significantly higher ASA scores. Several studies have also reported that laparoscopic gastrectomy is safe for elderly as well as for non-elderly patients in short-term surgical outcome (10,11,(33)(34)(35). In addition, we found no significant differences in intraoperative blood loss, operative time and complications after surgery between the elderly and non-elderly groups.…”
Section: Discussionsupporting
confidence: 65%
“…Patients who were more than 70 years old were categorized as elderly patients in 5 studies, [ 19 , 21 , 23 , 26 , 28 ] more than 65 years old in one studies, [ 25 ] and more than 75 years old in 5 studies. [ 18 , 20 , 22 , 24 , 27 ] According to the Newcastle-Ottawa Quality Assessment Scale, all 11 studies were achieved no less than 6 stars, Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…As we know, elderly GC patients, who are often malnourished and in a low state of immunity, with various comorbid conditions, have a high incidence of death from other diseases after surgeries. 4 , 5 , 39 - 41 Previous studies showed that the OS of elderly patients with a lower PNI score was shorter than the young. 42 The PNI could be a significant independent prognostic factor for predicting OS in elderly GC patients.…”
Section: Discussionmentioning
confidence: 99%